IMPLEMENTATION OF RAHN IN SHARIA GOLD FINANCING AT MODERN ISLAMIC FINANCIAL INSTITUTIONS (CASE STUDY IN BANK BRI SYARIAH BRANCH OF PEKANBARU). - AHMAD MAULIDIZEN (Hukum Islam, 2018)
Islamic Financing Products have started to grow rapidly in the current banking and financial industry at this time. This situation can be seen through the increase of Islamic banking assets for several years, in addition to the inclusion of more institutions offering Islamic products. Sharia Gold Pawn Products is the delivery of marhun (collateral goods) from the rahin (customers using mortgage financing) to the bank as a guarantee of part or all of the debt. This research is field (field research) with data collection method through observation, interview and documentation study in data collection. The author concludes that the application of Rahn's contract on Sharia gold mortgage financing at Bank BRI Syariah has been in accordance with the National Sharia Board Fatwa and there are several things that must be improved so as not to conflict with Sharia principles